INDONESIAN SEAS CEPHALOPODS : A COLLECTION OF FISHERIES LABORATORIES DIPONEGORO UNIVERSITY - Abdul Ghofar (JOURNAL OF COASTAL DEVELOPMENT, 1999)
A Study was conducted to describe the cephalopod fauna their regional distribution in the Indonesian seas. From specimen collection carried out since 1985 throughout the region, fourty four species were identified. The collection represents 11 loliginid squid, 3 sepiolids, 5 ommastrephids, 13 sepiids, 7 octopods, 2 argonautids,        2 nautiloids and 1 spirulid. Eleven identified species (or 25% of total) are evident to show a wide range of regional distribution, i.e. Loligo edulis, L. chinensis, L.duvauceli, L.sumatrensis, Sthenoteuthis oualaniensis, Sepioteuthis lessoniana, Abralia spaercki, Sepia latimanus, S.aculeata, S. pharaonis and Sepiella inermis,